Digoxigenin-Labeled In Situ Hybridization for the Detection of Streptococcus suis DNA in Polyserositis and a Comparison with Biotinylated In Situ Hybridization - CHAE, Chanhee; GOTTSCHALK, Marcelo; KIM, Sung-Hoon; KANG, Ikjae; SEO, Hwi Won; OH, Yeonsu; LEE, Jeehoon; PARK, Changhoon; YOU, Ok Heui (Journal of Veterinary Medical Science, 2014)
The objective of this study was to develop digoxigenin-labeled in situ hybridization (ISH) for the detection of Streptococcus suis in naturally infected pigs with polyserositis and to compare it with biotinylated ISH. Digoxigenin-labeled hybridization signals for S. suis were observed in cells that had infiltrated the fibrous polyserositis and microcolonies in the blood vessels. Mock hybridization showed no hybridization signals for endogenous digoxigenin. Biotinylated hybridization signals for S. suis were observed in cells that had infiltrated the fibrous polyserositis. However, similar hybridization signals were also observed in the fibrous inflammatory area using mock hybridization for endogenous biotin. The present study demonstrated that digoxigenin-labeled ISH is a valuable diagnostic tool for specific detection of S. suis in polyserositic tissues without nonspecific reactions compared with biotinylated ISH.